2021
DOI: 10.21203/rs.3.rs-1154283/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of Potential Distribution of Spodoptera Frugiperda In Northwest

Abstract: Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae), a newly invaded pest that breaks out fast and severely, causes a serious threat to the national security of food production. In this study, the MaxEnt model was used to predict the potentially suitable distribution area of S. frugiperda in Northwest China. The potential distribution of S. frugiperda was predicted using meteorological factors from the correlation analysis. According to the result, a satisfactory AUC value in the MaxEnt model indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…Hama Spodoptera frugiperda merupakan salah satu hama penting pada tanaman jagung (De Grootea, 2020;Li et al 2021). Gejala serangan awal akibat ulat grayak yaitu terlihat pada daun yaitu mnculnya gigitan halus larva berbentuk seperti jendela transparan yang memanjang yang bentuknya bervariasi dari kecil sampai kagak memanjang di permukaan daun.…”
Section: Hama Spodoptera Frugiperdaunclassified
“…Hama Spodoptera frugiperda merupakan salah satu hama penting pada tanaman jagung (De Grootea, 2020;Li et al 2021). Gejala serangan awal akibat ulat grayak yaitu terlihat pada daun yaitu mnculnya gigitan halus larva berbentuk seperti jendela transparan yang memanjang yang bentuknya bervariasi dari kecil sampai kagak memanjang di permukaan daun.…”
Section: Hama Spodoptera Frugiperdaunclassified
“…In the past few decades, pesticide use in China has shown an increasing trend, and the amounts of chemical insecticides used per unit area in the period 2016-2017 was several times higher than that in Western developed countries [9]. It has been reported that since Spodoptera frugiperda (J. E. Smith) invaded western Yunnan Province, China, the frequency of pesticide use in the area has shown an increasing trend [10]; new high-efficiency and low-toxicity pesticides, such as spinetoram, emamectin benzoate, chlorantraniliprole, acephate, and antibiotic pesticide spinosad, have played a successful role in controlling S. frugiperda [11]. At present, the control of P. gularis is mainly achieved through the spraying of chemical pesticides at the ear stage.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the FAWs invading China exhibit the highest host adaptability to maize [8,9]. In addition to maize, wheat has become an important wintering host plant of FAWs [10,11]. Furthermore, there have been reports of FAW infestations in rice fields across many areas of China [12][13][14].…”
Section: Introductionmentioning
confidence: 99%